Potencial celulolítico de Trichoderma longibrachiatum proveniente do rúmen bovino - Higor Alexandre Rodrigues Maia (2017)
Fungi of the ruminal microbiota present biotechnological potential, as they have cellulolytic activities that aid and promote the hydrolysis of the vegetal fiber. The fibrous vegetation is the basis of the ruminant diet and the degradation of the cell walls is fundamental to the digestive system of ruminants. In this research, the production of cellulases by Trichoderma longibrachiatum, from the ruminal fluid of cattle, was evaluated in submerged fermentation of Brachiaria decumbens or sugarcane bagasse. It was evaluated the growth of this fungus with two sources of nitrogen and the effect of the initial pH on the enzymatic production of T. longibrachiatum. Subsequently, we compared the potential of sugarcane bagasse and B. decumbens for the production of cellulases by the fungus. The fermentations were conducted in test tubes, in a medium fermentation containing Sabouraud broth, the nitrogen source and the carbon source packed in TNT sachets. The tubes were incubated on shaker bench with shaking at 120 rpm, at 39 ° C for ten days. The design was completely randomized and after the fermentations the final pH, fungal biomass, substrate dry matter degradation, total proteins and cellulolytic enzyme quantification were evaluated. It was verified that the fungus, in medium supplemented with ammonium sulfate, develops better and promoted better protein synthesis in medium with initial pH 4,5. The fermentative media containing B. decumbens produced larger concentrations of cellulases compared to those supplemented with sugarcane bagasse (P <0.05). The enzymatic extracts obtained with 24 hours of fermentation promoted greater release of total reducing sugars for both substrates. In this research, it was verified that the production of cellulases by the T. longibrachiatum isolate and its applications in the hydrolysis of lignocellulosic materials purposes are promising for animal feed supplementation for ruminants and for biotechnological.